Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/17511437211065611
|View full text |Cite
|
Sign up to set email alerts
|

CORONA (COre ultRasOund of covid in iNtensive care and Acute medicine) study: National service evaluation of lung and heart ultrasound in intensive care patients with suspected or proven COVID-19

Abstract: Background Combined Lung Ultrasound (LUS) and Focused UltraSound for Intensive Care heart (FUSIC Heart - formerly Focused Intensive Care Echocardiography, FICE) can aid diagnosis, risk stratification and management in COVID-19. However, data on its application and results are limited to small studies in varying countries and hospitals. This United Kingdom (UK) national service evaluation study assessed how combined LUS and FUSIC Heart were used in COVID-19 Intensive Care Unit (ICU) patients during the first wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Sixty‐five percent of scans led to a change in management. This finding is echoed by the larger ICS service evaluation data set 14 . Comparable interventions (e.g., fluid management, image requests and patient triage) were identified in 69% of patients in a larger observational study 33…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Sixty‐five percent of scans led to a change in management. This finding is echoed by the larger ICS service evaluation data set 14 . Comparable interventions (e.g., fluid management, image requests and patient triage) were identified in 69% of patients in a larger observational study 33…”
Section: Discussionmentioning
confidence: 95%
“…This finding is echoed by the larger ICS service evaluation data set. 14 Comparable interventions (e.g., fluid management, image requests and patient triage) were identified in 69% of patients in a larger observational study. 33 Introducing nurse-led PoCUS into routine ICU care may increase the availability of PoCUS for all ICU patients and contribute to timely changes in patient management 12 in a higher proportion of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serial ultrasonography using LUS and Focused UltraSound for Intensive Care heart (FUSIC Heart) were able to risk-stratify patients with COVID-19. The CORONA study found an association between LUS score, right ventricular dysfunction, and mortality ( 139 ).…”
Section: Discussionmentioning
confidence: 99%